2021
DOI: 10.1097/nrl.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Large Middle Cerebral Artery Ischemic Stroke in a Therapeutically Anticoagulated Patient With Severe SARS-CoV-2 Infection

Abstract: Introduction: Coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with hypercoagulability which can predispose infected patients to both arterial and venous thromboembolic complications. Despite therapeutic anticoagulation, there remains a risk of ischemic strokes, which may lead to adverse patient outcomes. Only a few cases are described in the literature regarding SARS-CoV-2 positive patients developing thrombotic ischemic strokes despite therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Those patients with a history of stroke had higher neutrophil levels, cardiac troponin I, D-dimers levels, NT pro-brain natriuretic peptide, IL-6, and lower lymphocyte and platelet counts in contrast to those without a history of stroke [157] . On the other hand, it has been demonstrated that the majority of patients with ischemic strokes have a hypercoagulability state induced by SARS-CoV-2 infection [157] , [158] . Other markers that indicate coagulopathy in patients with COVID-19 infection, in addition to D-dimer levels, include a slight increase in prothrombin-time (PT) activity, international normalized ratio (INR), partial thromboplastin time (PTT), platelet counts, thrombocytopenia, elevated lactate dehydrogenase (LDH), and fibrinogen [159] , [160] , [161] .…”
Section: Sars-cov-2 and Coagulation Disorders And Stroke Complicationmentioning
confidence: 99%
“…Those patients with a history of stroke had higher neutrophil levels, cardiac troponin I, D-dimers levels, NT pro-brain natriuretic peptide, IL-6, and lower lymphocyte and platelet counts in contrast to those without a history of stroke [157] . On the other hand, it has been demonstrated that the majority of patients with ischemic strokes have a hypercoagulability state induced by SARS-CoV-2 infection [157] , [158] . Other markers that indicate coagulopathy in patients with COVID-19 infection, in addition to D-dimer levels, include a slight increase in prothrombin-time (PT) activity, international normalized ratio (INR), partial thromboplastin time (PTT), platelet counts, thrombocytopenia, elevated lactate dehydrogenase (LDH), and fibrinogen [159] , [160] , [161] .…”
Section: Sars-cov-2 and Coagulation Disorders And Stroke Complicationmentioning
confidence: 99%
“…The main mechanism underlying the neurological complications of the virus is likely attributable to the state of systemic inflammation and hypercoagulability [ 3 , 4 ]. Moreover, according to recently reported cases, in patients with polymorbidity, standard anticoagulation may be insufficient to meet SARS-CoV-2-associated severe hypercoagulability syndrome and prevent the occurrence of cerebrovascular events [ 5 , 6 ]. In the pediatric field this topic is less discussed but published data have been growing recently.…”
Section: Introductionmentioning
confidence: 99%